Does migration raise agricultural investment? An empirical analysis for rural Mexico - Marcus Böhme (Kiel Institute for the World Economy (IfW), 2013)
The effect of remittances on capital accumulation remains a contested topic. This paper uses a panel data set from rural Mexico to investigate the impact of remittances on agriculture and livestock investments. After controlling for the endogeneity of migration through an instrumental variable estimation our empirical results show that international migration has a significantly positive effect on the accumulated agricultural assets but not on livestock capital. This suggests that households use the capital obtained from international migration only to overcome liquidity constraints for subsistence production whereas migration itself seems to be the superior investment option compared to other productive activities such as livestock husbandry.
Keywords: D1; J6; O1; 330; migration; investment; Mexico; agriculture